A Legal Review of Juvenile Criminal Offenses within the Indonesian Juvenile Justice System - Muh. Arsul Haq Sulthan; Ayu Safitri; Rudy (Masterpiece, 2026)
Children are an integral part of the nation’s future and therefore require special legal protection, particularly when they come into conflict with the law. Juvenile involvement in criminal offenses presents complex legal and social challenges, as children have not yet reached full psychological and emotional maturity. This study aims to examine the legal concept of juvenile criminal responsibility in Indonesia, identify the factors influencing children to commit criminal acts, and analyze the legal framework governing juvenile offenders under the Indonesian Juvenile Justice System. This research employs a normative legal research method with a literature-based approach, utilizing secondary data derived from statutory regulations, legal doctrines, court decisions, and relevant scholarly literature. The data were analyzed qualitatively and descriptively to provide a comprehensive legal interpretation. The findings indicate that juvenile criminal behavior is influenced by multiple interrelated factors, including economic hardship, family dysfunction, social environment, educational deficiencies, weak law enforcement, psychological vulnerability, and individual characteristics. Furthermore, Indonesian law, particularly Law Number 11 of 2012 on the Juvenile Criminal Justice System, emphasizes restorative justice and diversion as the primary approaches in handling juvenile cases. These mechanisms prioritize rehabilitation, social reintegration, and the best interests of the child rather than punitive measures. The study concludes that effective juvenile crime prevention and control require an integrated approach involving law enforcement agencies, families, educational institutions, and the community. Strengthening the implementation of diversion and restorative justice is essential to ensure legal protection while fostering the moral and social development of children